Dual roles and potential applications of exosomes in HCV infections - Yin, Yiqian; Zhao, Yuxue; Chen, Qiaoqiao; Chen, Yiwen; Mao, Lingxiang (Frontiers in Microbiology, 2022)
The hepatitis C virus (HCV) causes severe liver diseases, including hepatitis, liver cirrhosis, and hepatocellular carcinoma, which have high morbidity and mortality. Antibody targeting receptor-mediated HCV infections have limited therapeutic benefits, suggesting that the transmission of HCV infections is possibly mediated via receptor-independent mechanisms. Exosomes are membrane-enclosed vesicles with a diameter of 30–200 nm, which originate from the fusion of endosomal multivesicular bodies with the plasma membrane. Accumulating evidence suggests that exosomes have a pivotal role in HCV infections. Exosomes can transfer viral and cellular bioactive substances, including nucleic acids and proteins, to uninfected cells, thus spreading the infection by masking these materials from immunological recognition. In addition, exosomes originating from some cells can deliver antiviral molecules or prompt the immune response to inhibit HCV infection. Exosomes can be used for the diagnosis of HCV-related diseases, and are being presently evaluated as therapeutic tools for anti-HCV drug delivery. This review summarizes the current knowledge on the dual roles and potential clinical applications of exosomes in HCV infections.